Tapered fiber probe-based optical cardiac pacemaker - Xie, Yanzheng; Liu, Xiaoshuai (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe disorders of cardiac rhythm usually induce severe cardiovascular pathologies which might pose significant threats to human health. Although multiple cardiac pacing modalities have been developed, most of them face potential limitations including structural complexity, spatiotemporal imprecision and invasive implantation requirements, thereby constraining their widespread biomedical applications.MethodsBy leveraging the unique long-range focusing capability, we establish a tapered-fiber-probe (TFP) strategy enabling non-contact and highprecision near-infrared (NIR) optical pacing in zebrafish embryos, where sustained micron-scale spatial precision (3 μm FWHM) was achieved at physiologically relevant working distances.ResultsSystematic characterizations revealed developmental-stage-dependent pacing sensitivity, with pacing efficacy progressively decreasing during early cardiogenesis (36 dpf) and stabilizing upon cardiac maturation (≥6 dpf). Meanwhile, anatomical mapping demonstrated 1.7-fold greater photosensitivity in sinoatrial regions compared to ventricular myocardium. Calcium imaging confirmed a photothermal mechanism wherein optical absorption of irradiated myocardial tissue activates thermosensitive protein channels, triggering calcium ion influx and subsequent depolarization.DiscussionThe proposed strategy enables spatiotemporally precise cardiac conduction and establishes a proof-of-concept platform for non-contact optical pacing in zebrafish embryos, which might provide potential bio-optical tool development for basic arrhythmia research in vivo.